2015
DOI: 10.1111/jphp.12342
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of fermented ginseng and its major constituent compound K in a rat model of paracetamol (acetaminophen)-induced liver injury

Abstract: FG was shown to possess hepatoprotective activity against paracetamol (APAP)-induced liver injury better than FRG. Compound K might play an important role for an anti-inflammatory activity of FG by inhibiting JNK signalling in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Thus, ingesting the pre‐metabolized active ingredients of ginsenosides is expected to be more effective. Based on this idea, fermented ginseng (FG) containing an increased amount of compound K (CK) was produced by combining ginseng with Lactobacillus paracasei A221 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ingesting the pre‐metabolized active ingredients of ginsenosides is expected to be more effective. Based on this idea, fermented ginseng (FG) containing an increased amount of compound K (CK) was produced by combining ginseng with Lactobacillus paracasei A221 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, recent studies reported multiple pharmacological functions of deglycosylated ginsenosides including IH‐901, ginsenoside F 2 , ginsenoside Rg 3 , and ginsenoside Rh 2 such as anticarcinogenic, antidiabetic, anti‐allergic, anti‐inflammatory, and hepatoprotective effects. These functions were demonstrated by both in vitro and in vivo experiments (Park and others ; Guan and others ; Kim and others ; Igami and others ). Moreover, the skin care effects such as antimelanogenic, skin whitening, and antiwrinkle effects of the metabolites were demonstrated.…”
Section: Discussionmentioning
confidence: 83%
“…This result may be explained by compound K, one of the major ginsenoside constituents of fermented ginseng, playing an anti-inflammatory role by inhibiting signal transmission of JNK in the liver (30). Kim et al reported (31) that oxidative stress in the liver leads to inflammation via JNK activation, promoting inflammatory cytokine production.…”
Section: Discussionmentioning
confidence: 99%